If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -3y = 28 Solving 19 + -3y = 28 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -3y = 28 + -19 Combine like terms: 19 + -19 = 0 0 + -3y = 28 + -19 -3y = 28 + -19 Combine like terms: 28 + -19 = 9 -3y = 9 Divide each side by '-3'. y = -3 Simplifying y = -3
| 2(4a+1)=10 | | 99=2t-13t | | (-14)-12= | | 5x+9y=180 | | 4y+5=-5y+40 | | 4(1-r)-7r=-38-4r | | 9x+10-8x=11 | | 3+65x=39x+7 | | 12(2x-7)=10 | | 5z^2-10z+25=0 | | -8(3x-2)+4x= | | 4(1-8f)=-28 | | 4y-12x=-32 | | 15x-40=5 | | -3(3+7x)-3x=111 | | 35+4y-7=12y-14-2y | | (-12)-5= | | 70-2x=7-9x | | Y-12x=45 | | 1540=(2x)(x)(x-3) | | y+3*0=0 | | -2+4x=-8+37x | | -8(-4-2b)= | | (-12)-3= | | 3x+12=-23-2x | | 0+3x=0 | | X=36-y | | 2(s+6)= | | 5x+2xy=m | | 8(-5c+2)-3c= | | Z=36-y | | .10(a-4)=.20(3-2a) |